ADMINISTRATIVE PENAL LAW DALAM PENEGAKAN HUKUM LINGKUNGAN BERDASARKAN UNDANG-UNDANG CIPTA KERJA - Zuhdi Arman; Riko Riyanda (Fakultas Hukum, Universitas Samudra, 2022)
Environmental law enforcement in Indonesia is affected by Law Number 11 of 2020, which was passed to make it easier for investors to make investments in Indonesia by creating jobs.The purpose of this study is to determine the relationship between changes in environmental law enforcement in Indonesia following the passage of the Job Creation Law and changes in administrative penal law.This study employs normative law methods and literature study methods, which are followed by descriptive analysis methods.This study's findings demonstrate that Indonesia's environmental law enforcement has shifted under the Administrative Penal Law No. 32 of 2009, resulting in a regressive and ineffective approach to environmental protection and management.This is due to the fact that, following the passage of the Job Creation Law, most provisions for violations of administrative environment law first apply administrative sanctions.Aside from that, violations of administrative law that have an effect on the environment are the only ones that are eligible for criminal penalties.The characteristics of pollution and environmental damage that did not manifest at the time of the violation but many years later are not taken into account by the amendments to these provisions.